Teachers’ attitudes towards student-centered pedagogy and assessment practices: instruction efficacy in perspective - Mohd Nazim; Ali Abbas Falah Alzubi; Abdul-Hafeed Fakih (Institute of Advanced Engineering and Science, 2024)
The advancement of students’ knowledge, skills, and other learning experiences is the goal of student-centered pedagogy and assessment practices, and teachers’ attitudes toward implementing these principles are vital to ensure classroom instruction efficacy. From this standpoint, this study aimed to examine English as a foreign language (EFL) teachers’ attitude toward student-centered pedagogy and assessment practices in the Saudi EFL context concerning classroom instruction efficacy. Also, it correlated the participants’ responses with their gender, experience, degree, and specialization. The descriptive survey design was used to achieve the study objectives. The study tools, a questionnaire and a semi-structured interview were applied to a convenient sample of 73 faculty members. The results showed that the study sample (EFL teachers) had very positive attitudes towards pedagogy and assessment practices focused on students. In addition, the demographic variables of gender, experience, degree, and specialization had no significant role in affecting their responses to pedagogy and assessment practices. Finally, the interviewees expressed that the EFL classroom instruction efficacy can improve the situation in which students are more active, cooperative, responsible, engaged, communicative, and free. In light of the current results, the researchers proposed recommendations and implications.